Citrus varieties enriching fruit industry - Dubey, A K; Srivastav, Manish; Sharma, R M; Awasthi, O P; Verma, M K; Kaur, Charanjit; Singh, Dinesh (Indian Horticulture, 2019)
The productivity of citrus in our country is low as compared to other countries. Hence in modern citriculture, development of highly adaptable varieties with high fruit quality is the need of the day. Therefore, Scientists of IARI, New Delhi, have developed two new varieties, one of sweet orange and other of acid lime. Both are very timely released varieties.